The Witch (English Edition) - Freida McFadden (Hollywood Upstairs Press, 2026)
A brand-new, haunting thriller from Freida McFadden, #1 New York Times bestselling author of The Housemaid!Some secrets don't die―they wait.When Julia Barlow loses her job and her apartment, she has nowhere left to go but Pemberton, her family's sprawling seventeenth-century estate in rural Massachusetts. Officially, she's there to check in on her aging grandmother. Unofficially, she's hoping the old house will give her a place to disappear.Instead, Pemberton begins to unravel her.Every night, the grandfather clock stops at exactly 3:41 a.m. The lights flicker without warning. And a disembodied voice cries for help outside Julia's bedroom door.As Julia digs into the house's dark history, she uncovers the story of a woman executed for witchcraft in 1692―and realizes the past may not be finished with Pemberton yet. When decades of family lies begin to surface, Julia must confront a terrifying truth: Pemberton may be haunted by women whose voices refuse to stay silent.From #1 New York Times bestselling author Freida McFadden comes The Witch, a chilling, twist-filled thriller about secrets―those we inherit, those we bury, and those people will burn to keep silent.
Droits : Source Livre via Amazon
Keywords: witch english; english edition; edition; pemberton; historical; Ebooks Kindle